Improving the in vitro digestibility of rice starch by thermomechanically assisted complexation with guar gum - He, Hai; Chi, Chengdeng; Xie, Fengwei; Li, Xiaoxi; Liang, Yi; Chen, Ling (Food hydrocolloids, 2020)
The effects of thermomechanical treatment and guar gum (GG) addition on the in vitro digestibility of rice starch have been investigated. Rice starch added with GG at concentrations of 0, 0.025, 0.05, 0.075, or 0.10 g/100 g (wet basis) was subject to a micro-extrusion process. The in vitro digestibility, predicted glycemic index (pGI), and multi-scale structures (granule, lamellar, crystalline, and molecular structures) were examined. Micro-extruded rice starch (MERS) with GG presented reduced digestion rate and pGI, a higher degree of structural ordering, and altered crystalline, single-helical and double-helical structures. Using Pearson correlation analysis, the relationships among extrusion, the molecular interaction and multi-scale structure, and the digestibility were established. The content of resistant components (RC) was positively correlated with crystallinity (r = 0.836, p < 0.05), fractal dimension (r = 0.966, p < 0.05), A-type crystallinity (r = 0.954, p < 0.01), V-type crystallinity (r = 0.987, p < 0.05), R1045/1022 (r = 0.987, p < 0.05), single-helix content (r = 0.897, p < 0.05), and double-helix content (r = 0.991, p < 0.01); and was negatively correlated with pGI (r = −0.947, p < 0.05). Overall, this study showed that thermomechanical treatment assisted the complexation of GG with starch, which could be an effective means to improve the resistant properties of rice starch. [Display omitted] •Micro-extruded rice starch (MERS) was prepared with guar gum (GG).•GG addition enhanced slowly-digestible (SDC) and resistant (RC) components in MERS.•MERS with GG presented reduced digestion rate and predicted glycemic index (pGI).•Crystallinity and helical structures contributed to SDC and RC in MERS with GG.